A Sensitive and Specific Liquid Chromatography-Tandem Mass Spectrometry Assay for Simultaneous Quantification of Salivary Melatonin and Cortisol: Development and Comparison With Immunoassays - Shin, Sunghwan; Oh, Hyeonju; Park, Hea Ree; Joo, Eun Yeon; Lee, Soo-Youn (Annals of laboratory medicine, 2021)
Melatonin and cortisol are clinically important for diagnosing sleep and mood disorders. We developed and validated a liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay for simultaneous measurement of salivary melatonin and cortisol concentrations according to the Clinical and Laboratory Standards Institute guidelines. Additionally, we compared the LC-MS/MS assay with immunoassays, ELISA (Direct Salivary Melatonin Elisa EK-DSM, Bühlmann Laboratories AG, Schönenbuch, Switzerland) and electrochemiluminescence immunoassay (Cortisol II, Roche, Mannheim, Germany), using 121 saliva samples. The LC-MS/MS assay exhibited good performance in terms of linearity, precision, accuracy, limit of detection, lower limit of quantification, extraction recovery, carry-over, and matrix effect. The LC-MS/MS assay and immunoassays showed strong correlation (Pearson's r=0.910 for melatonin, r=0.955 for cortisol), but demonstrated a significant mean bias of 23.2% (range 54.0-143.7%) for melatonin and 48.9% (range 59.7-184.7%) for cortisol. Our LC-MS/MS assay provided more sensitive and reliable salivary melatonin and cortisol quantification results compared with immunoassays.